Structure-based mechanism of preferential complex formation by apoptosis signal-regulating kinases - Trevelyan, Sarah J; Brewster, Jodi L; Burgess, Abigail E; Crowther, Jennifer M; Cadell, Antonia L; Parker, Benjamin L; Croucher, David R; Dobson, Renwick C J; Murphy, James M; Mace, Peter D (Science signaling, 2020)
Apoptosis signal-regulating kinases (ASK1, ASK2, and ASK3) are activators of the p38 and c-Jun N-terminal kinase (JNK) mitogen-activated protein kinase (MAPK) pathways. ASK1-3 form oligomeric complexes known as ASK signalosomes that initiate signaling cascades in response to diverse stress stimuli. Here, we demonstrated that oligomerization of ASK proteins is driven by previously uncharacterized sterile-alpha motif (SAM) domains that reside at the carboxy-terminus of each ASK protein. SAM domains from ASK1-3 exhibited distinct behaviors, with the SAM domain of ASK1 forming unstable oligomers, that of ASK2 remaining predominantly monomeric, and that of ASK3 forming a stable oligomer even at a low concentration. In contrast to their behavior in isolation, the ASK1 and ASK2 SAM domains preferentially formed a stable heterocomplex. The crystal structure of the ASK3 SAM domain, small-angle x-ray scattering, and mutagenesis suggested that ASK3 oligomers and ASK1-ASK2 complexes formed discrete, quasi-helical rings through interactions between the mid-loop of one molecule and the end helix of another molecule. Preferential ASK1-ASK2 binding was consistent with mass spectrometry showing that full-length ASK1 formed hetero-oligomeric complexes incorporating large amounts of ASK2. Accordingly, disrupting the association between SAM domains impaired ASK activity in the context of electrophilic stress induced by 4-hydroxy-2-nonenal (HNE). These findings provide a structural template for how ASK proteins assemble foci that drive inflammatory signaling and reinforce the notion that strategies to target ASK proteins should consider the concerted actions of multiple ASK family members.